Central Bank Policy and Cryptocurrencies - Krivoruchko, Svetlana; Ponamorenko, Vladislav; Nebera, Anatoly (Journal of Reviews on Global Economics, 2018)
: Private cryptocurrencies became an integral part of the financial market. Central banks expressed various positions with respect to cryptocurrency from strong denial to non-intervention. We found out a common and dominating trend in the central bank's policy to lead the further development of crypto-currency by restrictions, robust surveillance and licensing. The first section contains common information about central banks's approach to regulation cryprocurrencies. Next section summarizes the treatment of cryptocurrency by central bankers, also it cointains 2 tables devoted to typology of cryptocurrency legality by countries and recognition of cryptocurrency by countries. Section 3 is devoted to the impact of global crisis on the dissemination of digital cryptocurrencies and contains 5 tables with information about banknotes and coins in circulation and a tables with top-10 cryptocurrencies. Section 4 describes the typology of warning signals sent by central banks to general public, investors, and market players. Section 5 concludes the material.